Comportamientos y manejo de la abstinencia alcohólica - Araujo Mayorga, Christian Rafael (2025)
Alcohol withdrawal manifests itself through various mental and physical symptoms that can cause considerable discomfort, this condition appears when a person with alcohol dependence decreases or ceases its consumption, the symptoms related to withdrawal, the available treatment alternatives and the temporal evolution of these symptoms, all of them related to problematic behaviors, are analyzed. Objective: To carry out an updated bibliographic review on the adequate management of alcohol withdrawal to improve the assistance to these patients. Methodology: The methodology adopted in the study is predominantly qualitative, non-experimental, of descriptive type with an analytical-descriptive scope, where the analysis of scientific documents of the empirical level and diverse scientific sources were used. Results: It was determined that everyone may experience withdrawal syndrome differently due to the variability of symptoms and their manifestation, which makes diagnosis and effective management difficult. Conclusions: This study has shown that symptoms can range from mild discomfort to life-threatening complications, for which early diagnosis and appropriate treatment is important. A multidisciplinary approach integrating medical, psychological and social care, together with the use of medications and specific therapies, such as cognitive-behavioral therapy and self-help group support, is crucial to reduce adverse effects.